Tax Digitalization and MSME Tax Compliance in Indonesia: A Systematic Literature Review of Empirical Studies - Dwi Indriani Fidiastutik Wijaya; Candra Pramula Pinandita; Rahma Rina Wijayanti; Endro Sugiartono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the relationship between tax digitalization and tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia using a Systematic Literature Review (SLR) approach based on PRISMA guidelines. This study reviews 15 empirical studies published in SINTA indexed journals during the period 2021-2025. The findings show that tax digitalization generally has a positive impact on MSME tax compliance by improving efficiency, convenience, and transparency in tax administration. However, the results are not fully consistent, as some studies report insignificant or indirect effects, indicating that the relationship is contextual. The effectiveness of tax digitalization is influenced by several key factors, including service and system quality, digital and tax literacy, taxpayer morale, and technological readiness. This study concludes that tax digitalization has strong potential to enhance MSME tax compliance, but its success depends on the readiness of supporting factors. Therefore, policy efforts should focus not only on technological development but also on strengthening user capacity and supporting ecosystems to achieve sustainable compliance.